Literature Review: Study of the Effect of Distributive Justice on Employee Performance - Rahma, Aulia; Tjahjono, Heru Kurnianto; Rahayu, Meika Kurnia Puji (Asian Journal of Management Analytics, 2024)
This paper aims to identify research trends on distributive justice on employee performance globally. The method used in this study is qualitative research with a bibliometric analysis. As for the data found, 107 documents were obtained and analyzed from 2014-2023. This dataset was converted to CSV format and for Bibliometrix in the analysis using VOSviewer. The study included publication distribution year, country, keywords, and authors. This study shows that the research trend from 2014 to 2023 indexed by Scopus has increased. 2020 and 2022 are the years with the highest number of research publications in the distributive justice and employee performance theme. The United States, with 28 documents, is considered the country that contributes the most to publications in this study. The study focuses on the influence of autonomous motivation on workplace performance, further emphasizing the importance of employee engagement and distributive justice. The results can help scholars quickly understand the distributive justice to employee performance research. The paper also provides an alternative approach to conducting a literature review with computer-aided analysis programs.